What Banks Do and Markets Don't: Cross-subsidization - Thorsten Koeppl; James MacGee (Queen's University, Department of Economics, 2005)
We show that interbank markets are a poor substitute for ``broad'' banks that operate across regions or sectors. In the presence of regional or sectoral asset and liquidity shocks, interbank markets can distribute liquidity efficiently, but fail to respond efficiently to asset shocks. Broad banks can condition on the joint distribution of both shocks and, hence, achieve an efficient internal allocation of capital. This allocation involves the cross-subsidization of loans across regions or sectors. Compared to regional banks that are linked through well-functioning interbank markets, broad banks lead to higher levels of aggregate investment, higher output, and less fluctuations within regions. However, broad banks generate endogenously aggregate uncertainty.
Keywords: G21; G28; D80; E44; 330; Banking Restrictions; Interbank Markets; Universal Banking; Endogenous Uncertainty